2023
DOI: 10.1111/inm.13132
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and mental health nursing: An integrative review of updated evidence

Abstract: Mental health nursing work is challenging, and workplace stress can have negative impacts on nurses' well‐being and practice. Resilience is a dynamic process of positive adaptation and recovery from adversity. The aims of this integrative review were to examine and update understandings and perspectives on resilience in mental health nursing research, and to explore and synthesize the state of empirical knowledge on mental health nurse resilience. This is an update of evidence from a previous review published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
5
7
0
Order By: Relevance
“…There are no directly comparable transition findings in mental health nursing, but these findings are also somewhat consistent with general graduate transition programs in nursing; however, the prevalence of well-being and resilience of graduates in the review of transition programs by Jarden, Jarden, Weiland, Taylor, Bujalka, et al (2021) (using different measures) was reported as high (rather than moderate). We also found moderate positive associations between well-being and resilience, which is generally consistent with review findings on mental health nurses' well-being and resilience across studies (Bui et al, 2023), and with those of Delgado et al (2021) although they reported strong positive associations. The weak negative association between well-being and turnover intention is broadly consistent with the wider transition literature (Jarden, Jarden, Weiland, Taylor, Bujalka, et al, 2021) but not previously reported in mental health nursing literature and warrants further investigation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…There are no directly comparable transition findings in mental health nursing, but these findings are also somewhat consistent with general graduate transition programs in nursing; however, the prevalence of well-being and resilience of graduates in the review of transition programs by Jarden, Jarden, Weiland, Taylor, Bujalka, et al (2021) (using different measures) was reported as high (rather than moderate). We also found moderate positive associations between well-being and resilience, which is generally consistent with review findings on mental health nurses' well-being and resilience across studies (Bui et al, 2023), and with those of Delgado et al (2021) although they reported strong positive associations. The weak negative association between well-being and turnover intention is broadly consistent with the wider transition literature (Jarden, Jarden, Weiland, Taylor, Bujalka, et al, 2021) but not previously reported in mental health nursing literature and warrants further investigation.…”
Section: Discussionsupporting
confidence: 89%
“…There was overall moderate well-being and resilience across this group of transition nurses. The finding on resilience is generally consistent with scores reported across studies in mental health nursing, which were moderate-high (Bui et al, 2023).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Qualitative findings suggest that nurses from many different clinical settings regularly engage in self‐regulation (such as creating emotional barriers or professional boundaries) using available resources (personal or workplace social supports) to maintain their resilience and manage workplace stress (Cooper et al, 2021). In the specialty field of mental health nursing, there is a growing body of evidence on resilience, but limited qualitative studies and none during COVID‐19 (Bui et al, 2023; Foster et al, 2019). Most recently, Delgado et al (2022) investigated the resilient processes MHNs drew on when engaging in emotional labour in their work.…”
Section: Introductionmentioning
confidence: 99%